A Behavioral Theory of the Firm: Specifics of Czech Entrepreneurial Behavior - Mandysová, Ivana (My University, 2018)
The article attempts to present empirically relevant, process-oriented behavioral theory of the firm incorporating Czech specific characteristics of entrepreneurial behavior. It conceptually reconciles the reality by looking at the original ideas of ‘A Behavioral Theory of the Firm’ by Cyert and March. Study critically examines available theoretical models of firm’s rational behavior investigated in heuristic theories. These models offer an interpretation of entrepreneurial behavior as a product of personal preferences and characteristics. A theoretical re-orientation towards recognition of entrepreneurial behavior is developed and illustrated. Contemporary research outcomes coincide that the emerging, probably eclectic, paradigm strongly emphasizes the role and quality of human capital including the entrepreneur´s skills. Study is based on in-depth qualitative empirical research and subsequently it derives from statistically established theoretical patterns. It explores and explains the way entrepreneurs make economic decisions, their actions and counteractions with business environment, while, at the same time, focusing on Czech specifics. Firms have proved exceptional flexibility and have succeeded in counteracting and even manipulating the shortcomings and disadvantages of business environment. They have exploited chances and grasp opportunities in spite of additional expenditures that increased their costs. It has been proved that decisions are not made according to designed strategic plans aimed at the achievement of goals and permanent profit increase. Research has discovered that behavioral patterns further offer an access to specialized inputs, discovered relations proved to provide the entrepreneur with access to knowledge and information, even though bounded rationality and imperfect knowledge often lead to satisfactory solution and are typical for Czech firms. To create a dynamic economy, which ensures that entrepreneurs can start and develop their businesses, public policy should understand entrepreneurship, support it, provide relevant public goods and motivate it properly.
Behaviorální teorie firmy: specifika chování českých podnikatelů
Keywords: Entrepreneur; management; decision making; Czech business environment specifics.; Podnikatel; management; rozhodování; české podnikatelské prostředí - specifika.